Senescent tumor cells in colorectal cancer are characterized by elevated enzymatic activity of complexes 1 and 2 in oxidative phosphorylation - Jun Sang Shin; Tae-Gyu Kim; Young Hwa Kim; So Yeong Eom; So Hyun Park; Dong Hyun Lee; Tae Jun Park; Soon Sang Park; Jang-Hee Kim (Journal of Pathology and Translational Medicine, 2023)
Background Cellular senescence is defined as an irreversible cell cycle arrest caused by various internal and external insults. While the metabolic dysfunction of senescent cells in normal tissue is relatively well-established, there is a lack of information regarding the metabolic features of senescent tumor cells. Methods Publicly available single-cell RNA-sequencing data from the GSE166555 and GSE178341 datasets were utilized to investigate the metabolic features of senescent tumor cells. To validate the single-cell RNA-sequencing data, we performed senescence-associated β-galactosidase (SA-β-Gal) staining to identify senescent tumor cells in fresh frozen colorectal cancer tissue. We also evaluated nicotinamide adenine dinucleotide dehydrogenase–tetrazolium reductase (NADH-TR) and succinate dehydrogenase (SDH) activity using enzyme histochemical methods and compared the staining with SA-β-Gal staining. MTT assay was performed to reveal the complex 1 activity of the respiratory chain in in-vitro senescence model. Results Single-cell RNA-sequencing data revealed an upregulation in the activity of complexes 1 and 2 in oxidative phosphorylation, despite overall mitochondrial dysfunction in senescent tumor cells. Both SA-β-Gal and enzyme histochemical staining using fresh frozen colorectal cancer tissues indicated a high correlation between SA-β-Gal positivity and NADH-TR/SDH staining positivity. MTT assay showed that senescent colorectal cancer cells exhibit higher absorbance in 600 nm wavelength. Conclusions Senescent tumor cells exhibit distinct metabolic features, characterized by upregulation of complexes 1 and 2 in the oxidative phosphorylation pathway. NADH-TR and SDH staining represent efficient methods for detecting senescent tumor cells in colorectal cancer.